2021
DOI: 10.1186/s12866-021-02264-5
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum strains isolated from spontaneously fermented cocoa exhibit potential probiotic properties against Gardnerella vaginalis and Neisseria gonorrhoeae

Abstract: Background Probiotics are important tools in therapies against vaginal infections and can assist traditional antibiotic therapies in restoring healthy microbiota. Recent research has shown that microorganisms belonging to the genus Lactobacillus have probiotic potential. Thus, this study evaluated the potential in vitro probiotic properties of three strains of Lactiplantibacillus plantarum, isolated during the fermentation of high-quality cocoa, against Gardnerella vaginalis and Neisseria gonor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Lactiplantibacillus plantarum (formerly Lactobacillus plantarum ), which is a homofermentative lactic acid bacterium (LAB), has been widely applied as a model species for ecological, metabolic, and genetic studies in lactobacilli ( Zheng et al, 2020 ). In addition, L. plantarum is used as a starter culture in multiple food and beverage fermentations and as a probiotic for both animals and humans, making it of considerable academic and economic importance ( das Neves Selis et al, 2021 ). L. plantarum has been classified as a “nomadic” or “generalist” bacterium because of its diverse habitats ( Martino et al, 2016 ; Choi et al, 2018 ; Yu et al, 2020 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lactiplantibacillus plantarum (formerly Lactobacillus plantarum ), which is a homofermentative lactic acid bacterium (LAB), has been widely applied as a model species for ecological, metabolic, and genetic studies in lactobacilli ( Zheng et al, 2020 ). In addition, L. plantarum is used as a starter culture in multiple food and beverage fermentations and as a probiotic for both animals and humans, making it of considerable academic and economic importance ( das Neves Selis et al, 2021 ). L. plantarum has been classified as a “nomadic” or “generalist” bacterium because of its diverse habitats ( Martino et al, 2016 ; Choi et al, 2018 ; Yu et al, 2020 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because the supernatant in treatment 1 was heated, it was assumed that any antimicrobial peptides present would become inactive [53], leaving organic acids, hydrogen peroxide (H 2 O 2 ), and alcohol as the bioactive components that inhibited N. gonorrhoeae. A recent study demonstrated that probiotic Lactiplantibacillus plantarum strains isolated from spontaneously fermented cocoa may possess antimicrobial activity against N. gonorrhoeae [54]. Additionally, this probiotic was discovered to produce H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobials produced by lactobacilli are quite diverse and fall within two main chemical categories, proteinaceous and non-proteinaceous substances. Data reported in Table 1 and Table 2 show that the antimicrobial activity of L. plantarum is mainly exerted by bacteriocins (~60% of the reported strains) or partially characterised proteinaceous compounds, followed by organic acids or acidic conditions (i.e., acid CFS [ 25 ]), and biosurfactants (BS) such as glycoproteins and EPS.…”
Section: Nature and Mechanisms Of L Plantarum Antimicrobialsmentioning
confidence: 99%
“…Since the growth of important food-spoilage and food-poisoning microorganisms is inhibited at low pH (<4), L. plantarum , which is one of the lactobacilli with the highest lactic acid production rate [ 25 , 68 ], can be added to many fermented foods as a natural preservative [ 69 , 70 ]. LAB, including L. plantarum , may be homofermentative or heterofermentative depending on the pathway used for glucose fermentation.…”
Section: Nature and Mechanisms Of L Plantarum Antimicrobialsmentioning
confidence: 99%
See 1 more Smart Citation